Immune‐complex level of cofilin‐1 in sera is associated with cancer progression and poor prognosis in pancreatic cancer. Issue 4 (April 2017) - Satoh, Mamoru; Takano, Shigetsugu; Sogawa, Kazuyuki; Noda, Kenta; Yoshitomi, Hideyuki; Ishibashi, Masumi; Mogushi, Kaoru; Takizawa, Hirotaka; Otsuka, Masayuki; Shimizu, Hiroaki; Miyazaki, Masaru; Nomura, Fumio
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal malignancies. To improve its outcome, reliable biomarkers are urgently needed. In this study, we aimed to elucidate the key molecules involved in PDAC progression using proteomics approaches. First, we undertook 2‐D electrophoresis to identify the proteins overexpressed in PDAC tissues. Following the analysis of agarose gel spots, cofilin‐1 was identified and verified as a candidate protein commonly upregulated in PDAC tissues. In immunohistochemistry, cofilin‐1 was strongly expressed in the cytoplasm of PDAC cells. Samples were divided into two groups based on the level of cofilin‐1 expression. The high expression group showed significantly higher incidence of hematogenous dissemination in relapsed patients than the low expression group ( P = 0.0083). In in vitro experiments, knockdown of cofilin‐1 significantly decreased chemotaxis in PDAC cell lines. After we confirmed that cofilin‐1 was secreted from PDAC cells, we established a detection system for the immune‐complex of cofilin‐1 in sera. Using this system, we measured the IC levels of cofilin‐1 in sera and observed that the IC levels of cofilin‐1 in PDAC patients were higher than those in healthy volunteers and patients with pancreatitis (PDAC vs . healthy volunteers, P < 0.0001; PDAC vs . patients with pancreatitis, P < 0.026). Notably, the IC levels of cofilin‐1 showed a stepwise increase during PDAC progression ( P = 0.0034), and high IC levels of cofilin‐1 indicated poor prognosis of patients after surgery ( P = 0.039). These results suggest that the IC of cofilin‐1 in sera is a potentially attractive serum biomarker for the prognosis of PDAC. Abstract : High cofilin‐1 expression is associated with hematogenous dissemination in recurrence forms of pancreatic cancer (PDAC) patients. The immune‐complex (IC) levels of cofilin‐1 in sera of PDAC patients were higher than those in sera of healthy volunteers and patients with pancreatitis. The IC levels of cofilin‐1 showed a stepwise increase during PDAC progression, and high IC levels of cofilin‐1 indicated poor prognosis of patients after surgery.